Analisis Pengaruh Media Informasi Terhadap Perilaku Gizi Seimbang Mahasiswa FKIK UINAM 2021 (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2022)
Media information is a medium that can make it easier to find out information widely. This study aims to determine the effect of information media on balanced nutrition behavior in FKIK UINAM 2021 students. This study uses a quantitative research type with a cross sectional approach. The population in this study were all students of FKIK UINAM Class of 2018-2020. The number of samples as many as 182 with a sampling technique using purposive sampling. sample size using the Lemeshow formula. The research instrument is a questionnaire. Data analysis using chi-square test. The results of the study found that there was an relationship between good information media and good behavior on balanced nutrition with the results of the chi square statistic test obtained p-Value 0.004. so it can be concluded that the better we get information about balanced nutrition, the better our behavior in implementing balanced nutrition will be. . This is because when someone gets information, the knowledge about balanced nutrition increases so that they can apply balanced nutrition behavior properly. Researchers recommend to students to be more intense in seeking information from various sources regarding balanced nutrition.